PELAKSANAAN BIMBINGAN DAN KONSELING KOMPREHENSIF DALAM PENDIDIKAN INKLUSIF - Gea, Leli Hayati; Munthe, Mondang; Lase, Famahato; Zebua, Elizama (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
Comprehensive guidance and counseling services are implemented in inclusive education. The aim of this research is to reveal whether and how comprehensive guidance and counseling services are carried out well, using quantitative methods, descriptive strategies to investigate circumstances, conditions or other things that have been mentioned in order to find out the value of independent variables, either one or more variables without making comparisons, or connect it with other variables and the results are described in the form of a research report. The research subjects were: (1) the school principal, (2) subject teachers, (3) guidance and counseling teachers, and (4) all class VII students whose sample was 6 people per group using the standardized random sampling technique. A sampling technique where the population is divided into several homogeneous subgroups based on certain characteristics, then random samples are taken from each stratum, namely a group of 3 smart students per class and a group of 3 low ability students per class. The research location is SMP Negeri 1 Tuhemberua. Research data was collected using closed questionnaires and interviews, the data was in the form of numbers and narratives to answer the research questions that had been asked. The results of the research revealed that 2 students had responses regarding the implementation of comprehensive guidance and counseling in inclusive education with low criteria, 23 people with medium criteria and 5 people with high criteria. The results of interviews with school principals, subject teachers, and guidance and counseling teachers show that the implementation of comprehensive guidance and counseling programs in inclusive education has not been implemented well due to the lack of training of guidance and counseling teachers in dealing with problems faced by students, lack of collaboration between subject teachers and guidance and counseling teachers, and There is no schedule for class attendance, there is a lack of adequate facilities to support guidance and counseling activities and students do not want to open up about the problems they are facing. It can be concluded that the implementation of comprehensive guidance and counseling in inclusive education at SMP Negeri 1 Tuhemberua has not been implemented well. It is recommended that guidance and counseling teachers plan and implement comprehensive guidance and counseling services, and school principals facilitate them and that students follow them well.